Microcin J25 Exhibits Inhibitory Activity Against Salmonella Newport in Continuous Fermentation Model Mimicking Swine Colonic Conditions - Naimi, Sabrine; Zirah, Séverine; Taher, Menel Ben; Theolier, Jérémie; Fernandez, Benoît; Rebuffat, Sylvie Françoise; Fliss, Ismail (Frontiers in Microbiology, 2020)
Microcin J25 (MccJ25), a 21-amino acid bacteriocin produced by Escherichia coli (E. coli), is a potent inhibitor of Enterobacteriaceae, including pathogenic E. coli, Salmonella and Shigella. Its lasso structure makes it highly stable and therefore of interest as a possible antimicrobial agent in foods or as an alternative to antibiotics in livestock production. In the present study, we aimed to evaluate in vitro the inhibitory activity of MccJ25 against Salmonella enterica subsp. enterica serovar Newport ATCC 6962 (Salmonella Newport) used as a model pathogen under conditions simulating those of the swine proximal colon. The growth inhibition activity of MccJ25 against Salmonella Newport was examined in lysogenic broth (LB) and in modified MacFarlane medium that allows miming the swine colonic conditions. The MccJ25 activity was further determined using the Polyfermentor intestinal model (PolyFermS), an in vitro continuous fermentation model that permits deciphering the activity of any antimicrobial molecule in real colon fermentation conditions using selected microbiota. It was set up here to simulate the porcine proximal colon fermentation. In these conditions, the inhibition activity of MccJ25 was compared to those of two antimicrobial agents, reuterin and rifampicin. The minimal inhibitory concentration (MIC) of MccJ25 was determined at 0.03 µM in LB medium, compared to 1079 µM and 38 µM for reuterin and rifampicin, respectively, showing a significantly higher potency of MccJ25. Total inhibition of Salmonella Newport was observed in LB medium over 24 h of incubation at concentrations starting from the MIC. In the PolyFermS model, MccJ25 induced a significantly stronger inhibition of Salmonella Newport growth than reuterin or rifampicin. A specific and sensitive LC-MS method allowed to detect and quantify McJ25 in the PolyFermS fermentation system, showing that MccJ25 remains stable and active against Salmonella in conditions mimicking those found in swine colon. This study paves the way for further exploring the potential of this bacteriocin as an alternative to antibiotics in livestock.